Advance directive in a young patient: Palliative care in the context of grade 3 lupus nephritis (International Seven Journal of Health Research, 2024)
Systemic lupus erythematosus is an autoimmune systemic disease that compromises several organ systems, being able to reduce the quality of life of patients in many cases. Early diagnosis is associated with poor prognosis, since the period of activity of the disease is longer. Lupus nephritis is one of the consequences that can arise, and chronic kidney disease that follows becomes terminal in 10% of cases. The present study reports the case of a young patient, carrying lupus, with grade 3 lupus nephritis, who, in the face of the scarcity of resources that could alleviate her suffering and return her quality of life, chose not to receive advanced life support in future hospitalizations.